2012
DOI: 10.1210/en.2011-1795
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonist, Exendin-4, Regulates Feeding-Associated Neuropeptides in Hypothalamic Neurons in Vivo and in Vitro

Abstract: Exendin-4, a long-acting glucagon-like peptide-1 receptor (GLP-1R) agonist, is a potential regulator of feeding behavior through its ability to inhibit gastric emptying, reduce food intake, and induce satiety. GLP-1R activation by exendin-4 induces anorexia; however, the specific populations of neuropeptidergic neurons activated by exendin-4 within the hypothalamus, the central regulator of energy homeostasis, remain unclear. This study determines whether exendin-4 regulates hypothalamic neuropeptide expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 54 publications
3
32
0
2
Order By: Relevance
“…Acute EX-4-induced anorexia has been shown to be accompanied by activation of GLP-1R-expressing regions including the ARC, paraventricular nucleus, and dorsomedial nucleus of hypothalamus as assessed by c-Fos. Furthermore, double-labeling immunohistochemistry indicated that central EX-4 significantly activated POMC and NPY neurons in the ARC (56). In this study, we found that long-term EX-4 injection increased POMC and decreased NPY expression in both HF diet-fed rats and SC-fed rats.…”
Section: Discussionsupporting
confidence: 53%
“…Acute EX-4-induced anorexia has been shown to be accompanied by activation of GLP-1R-expressing regions including the ARC, paraventricular nucleus, and dorsomedial nucleus of hypothalamus as assessed by c-Fos. Furthermore, double-labeling immunohistochemistry indicated that central EX-4 significantly activated POMC and NPY neurons in the ARC (56). In this study, we found that long-term EX-4 injection increased POMC and decreased NPY expression in both HF diet-fed rats and SC-fed rats.…”
Section: Discussionsupporting
confidence: 53%
“…Our findings indicate that GLP-2R activation involves complex interactions between several hypothalamic nuclei, acute activation of feeding-related neuropeptidergic neurons, and longer-term transcriptional regulation of downstream neuropeptides. Central h(Gly 2 )GLP-2 administration activated several hypothalamic regions with a distinct pattern of c-Fos expression in comparison with the long-acting GLP-1R agonist, exendin-4 (47). Not only the major nuclei that lie in the vicinity of the third ventricle were activated but also the lateral hypothalamus was activated.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous comprehensive studies aim to describe the GLP-1R population responsible for GLP-1-induced energy intake reduction (20,(33)(34)(35)(36)(37)(38)(39)(40)(41). This task has been hampered by the widespread distribution of the GLP-1R in the brain and in the periphery on neurons that could rapidly signal to the brain.…”
Section: Discussionmentioning
confidence: 99%